Application of Rheumatic Gymnastics Therapy to Address Acute Rheumatic Pain Nursing Problems in the Elderly at Nursing Home: A Case Study - Zakiyah, Efadatus; Kurdi, Fahruddin; Rasni, Hanny; Bahtiar, Syahroni (Jurnal Kegawatdaruratan Medis Indonesia, 2023)
Rheumatism in the elderly occurs due to swollen joints, inflammation or damage caused by damaged joints and tense muscles. These changes include the presence of disease that causes damage to cartilage, degenerative joints and nearby bones, and can cause inflammation of the inner lining of the joint. Complaints that are often felt by someone who has arthritis are pain in the limbs, inflammation of the joints, joint stiffness, joint sounds. The purpose of this scientific work is to overcome the application of rheumatic gymnastic therapy in dealing with acute pain in rheumatic clients. The research method used was a case study through a process of assessment to evaluation of nursing related to acute pain experienced by rheumatism sufferers and given therapeutic interventions by rheumatic gymnastics. Rheumatic gymnastics is an alternative treatment for the health of the elderly body and trains the ability of joint muscles so that they do not experience joint stiffness, rheumatic gymnastics also prevents degenerative growth in aging, facilitates adjustments in health. Therapy was given for 3 days with a duration of 15 minutes, analyzed to find a reduced time in 30 minutes which was carried out at least 2 times in 1 week. And these exercises are very effective and in accordance with the energy released by the elderly. Physical exercise time that is carried out for more than 30 minutes can cause fatigue in the elderly which can cause discomfort. The results of the evaluation of the use of rheumatic gymnastics in reducing the client's acute pain were that after 3 days the evaluation of the client said it was better and in accordance with the outcome criteria where there were complaints of decreased pain. Suggestions for future researchers are expected to be able to develop the theory used and other therapies to reduce client fatigue levels.